International clinical guidelines for the management of phosphomannomutase 2-congenital disorders of glycosylation: Diagnosis, treatment and follow up - Altassan, Ruqaiah; Péanne, Romain; Jaeken, Jaak; Barone, Rita; Bidet, Muad; Borgel, Delphine; Brasil, Sandra; Cassiman, David; Cechova, Anna; Coman, David; Corral, Javier; Correia, Joana; et al. (Journal of inherited metabolic disease, 2019)
Phosphomannomutase 2 (PMM2-CDG) is the most common congenital disorder of N-glycosylation and is caused by a deficient PMM2 activity. The clinical presentation and the onset of PMM2-CDG vary among affected individuals ranging from a severe antenatal presentation with multisystem involvement to mild adulthood presentation limited to minor neurological involvement. Management of affected patients requires a multidisciplinary approach. In this article, a systematic review of the literature on PMM2-CDG was conducted by a group of international experts in different aspects of CDG. Our managment guidelines were initiated based on the available evidence-based data and experts' opinions. This guideline mainly addresses the clinical evaluation of each system/organ involved in PMM2-CDG, and the recommended management approach. It is the first systematic review of current practices in PMM2-CDG and the first guidelines aiming at establishing a practical approach to the recognition, diagnosis and management of PMM2-CDG patients.
Keywords: vrozené poruchy glykosylace; Congenital Disorders of Glycosylation; Phosphotransferases (Phosphomutases); fosfotransferasy (fosfomutasy); Follow-Up Studies; glykosylace; Humans; lidé; Glycosylation; následné studie